Acne Scar Management by Fractional CO2 Laser - Al-Bazzaz, Ali A.; Al Omary, Hanan L. (Iraqi Journal of Laser, 2019)
Acne scars are one of the most common problems following acne vulgaris. Despite the extensive list of available treatment modalities, their effectiveness depends upon the nature of the scar. Ablative lasers had been used to treat acne scars; one of them is the fractional CO2 laser. The aim of this study is to evaluate the outcome of fractional CO2 laser in the treatment of acne scars. Methods: Since January 2010 to June 2013, using 10600 nm fractional CO2 laser beams, the acne scar of 400 patients, 188 males and 212 females, mean age of 34 years, have been treated and classified according to severity into four grades following Goodman and Baron classification. Each patient underwent 3-5 sessions once monthly. The mean laser exposure time was 15 minutes, mean operative time was 1-1.5 hours, no hospital stay and the treatment coarse lasted 3-5 months. Patients were followed up for about one year to evaluate the success of the procedure. Results: Investigators and patients graded the improvement on a scale (0=no improvement to grade1 0-25%, grade 2, 25-50% ,grade 3 50-75%,grade 4 more than 75%. Both investigators and patients gave mean improvement scores in the range of 50% to 75% for scar depth, scar margins beveling, better color match, texture, skin tightness and overall improvement of the patients well looking. The degree of improvement increased with each treatment session and continued to increase between the 1-month and 3-month after the last treatment. Conclusion Fraction ablative resurfacing seems to hit a sweet spot between the minimal benefits of traditional nonablative laser treatment and the considerable downtime and complications of ablative resurfacing.